Content-aware texture deformation with dynamic control. (October 2020) - Guingo, Geoffrey; Larue, Frédéric; Sauvage, Basile; Lutz, Nicolas; Dischler, Jean-Michel; Cani, Marie-Paule
Highlights: Dynamic textures improve the appearance of 3D virtual objects across time. Textures are deformed in real-time on GPU without heavy simulation. The deformation is controlled by the geometry or by external factors. The deformation is finely defined at texel scale. Complex thin structures are correctly stretched and sampled. Abstract: Textures improve the appearance of virtual scenes by mapping visual details on the surface of 3D objects. Various scenarios – such as real-time animation, interactive texture modelling, or offline post-production – require textures to be deformed in a controllable and plausible manner. We propose a novel approach to model and control texture deformations, which is easy to implement in a standard graphics pipeline. The deformation is implemented at pixel resolution as a warping in the parametric domain. The warping is controlled locally and dynamically by real-time integration along the streamlines of a pre-computed flow field. We propose a technique to pre-compute the flow field from a simple scalar map representing heterogeneous dynamic behaviors. Moreover, to manage sampling issues arising in over-stretched areas during deformation, we provide a mechanism based on re-sampling and texture synthesis. Warping may alternatively be controlled by deformation of the underlying surface, environment parameters or interactive editing, which demonstrates the versatility of our approach.